Trajectories of frailty among Chinese older people in Hong Kong between 2001 and 2012: an age-period-cohort analysis. (8th December 2017) - Yu, Ruby; Wong, Moses; Chong, K C; Chang, Billy; Lum, C M; Auyeung, T W; Lee, Jenny; Lee, Ruby; Woo, Jean
Abstract: Background: there is little evidence to suggest that older people today are living in better health than their predecessors did at the same age. Only a few studies have evaluated whether there are birth cohort effects on frailty, an indicator of health in older people, encompassing physical, functional and mental health dimensions. Objectives: this study examined longitudinal trajectories of frailty among Chinese older people in Hong Kong. Methods: this study utilised data from the 18 Elderly Health Centres of the Department of Health comprising a total of 417, 949 observations from 94, 550 community-dwelling Chinese people aged ≥65 years in one early birth cohort (1901–23) and four later birth cohorts (1924–29, 1930–35, 1936–41, 1942–47) collected between 2001 and 2012, to examine trajectories of the frailty index and how birth cohorts may have contributed to the trends using an age-period-cohort analysis. Results: more recent cohorts had higher levels of frailty than did earlier cohorts at the same age, controlling for period, gender, marital status, educational levels, socioeconomic status, lifestyle and social factors. Older age, being female, widowhood, lower education and smoking were associated with higher levels of frailty. Conclusion: more recent cohorts had higher levels of frailty than did earlier cohorts. Frailty interventions, coupled with early detection, should be developed to combat the increasing rates of frailty in Hong Kong Chinese.